2020
DOI: 10.1016/j.celrep.2020.107750
|View full text |Cite
|
Sign up to set email alerts
|

TBC1D5-Catalyzed Cycling of Rab7 Is Required for Retromer-Mediated Human Papillomavirus Trafficking during Virus Entry

Abstract: Highlights d Traptamer screening identifies TBC1D5 as a human papillomavirus entry factor d TBC1D5 is a Rab7 GTPase-activating protein that activates retromer during HPV entry d Rab7 cycling between GTP-and GDP-bound forms is required for HPV entry d HPV trafficking displays different Rab7 requirements than cellular cargo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(82 citation statements)
references
References 62 publications
6
76
0
Order By: Relevance
“…How Rab7a mediates HPV trafficking remained unclear until recently. Using a protein interference screen, Xie et al (2020) identified that TBC1D5 was essential to HPV entry. The recruitment of TBC1D5 to the retromer–L2 protein complexes likely leads to the disassembly of the retromer–HPV complex through inactivation of Rab7a-GTP, thereby promoting the recycling of retromer.…”
Section: Hpv L2 and Tbc1d5mentioning
confidence: 99%
See 1 more Smart Citation
“…How Rab7a mediates HPV trafficking remained unclear until recently. Using a protein interference screen, Xie et al (2020) identified that TBC1D5 was essential to HPV entry. The recruitment of TBC1D5 to the retromer–L2 protein complexes likely leads to the disassembly of the retromer–HPV complex through inactivation of Rab7a-GTP, thereby promoting the recycling of retromer.…”
Section: Hpv L2 and Tbc1d5mentioning
confidence: 99%
“…Notably, Xie et al demonstrated that the cycling of Rab7a-GTP and Rab7a-GDP is required for HPV trafficking. In contrast, the cellular trafficking of CI-MPR and DMT1-II requires only Rab7-GTP ( Xie et al, 2020 ). These findings greatly expand our understanding the mechanisms by which HPV manipulates host cellular activity, and suggest that TBC1D5 inhibitors could suppress HPV infection.…”
Section: Hpv L2 and Tbc1d5mentioning
confidence: 99%
“…Traptamer genes were recovered from the DNA of proliferating cells and tested individually for their ability to inhibit expression of a reporter gene expressed from a different HPV16 virus. Details of library construction, selection, and traptamer recovery are described in [22].…”
Section: Traptamers That Inhibit Human Papillomavirus Entrymentioning
confidence: 99%
“…The ability of individual cloned traptamers to inhibit HPV infection is tested to confirm activity. Figure reproduced from Xie et al [22]. intracellular localizations, and inhibit HPV entry at different steps [23].…”
Section: Traptamers That Inhibit Human Papillomavirus Entrymentioning
confidence: 99%
“…Retromer is also a prominent target hijacked by intracellular pathogens to facilitate their transport and replication. This includes viruses such as SARS-CoV-2, human immunodeficiency virus (HIV), hepatitis C virus (HCV), and human papilloma virus (HPV) [58][59][60][61][62][63][64][65][66][67][68][69][70] , and intracellular bacteria such as Coxiella burnetii and Legionella pneumophila [71][72][73][74][75][76][77] . Mechanistic studies have shown that the secreted effector protein RidL from L. pneumophila binds directly to Vps29, competing with endogenous regulators TBC1D5 and VARP, inhibiting…”
Section: Introductionmentioning
confidence: 99%